THE USE OF METAPHORS AS SOCIAL CRITICISM IN BILLIE EILISH O’CONNELL AND FINNEAS O’CONNELL’S ALL THE GOOD GIRLS GO TO HELL AND THE BAD GUY - Hagung Yudistiro Utomo; Henny Suharyati; Sari Rejeki (Universitas Pakuan, 2022)
This study is aimed to identify the use of metaphors as social criticism in the songs All the good girls go to hell and Bad Guy by Billie Eilish O’Connel and Finneas O’Çonnel. The research approach in this study is descriptive qualitative. All the metaphors in the two songs indicate that the pattern of comparison or similarity is patterns of form and appearance, position in structure, function, and space and time. Furthermore, the classification of social criticism based on social problems are matters related to mental health and environmental issues. Metaphor functions not only as a medium for comparing or equating literal meaning with non-literal meaning, but it also functions as a medium for conveying social criticism in song lyrics.Keywords: figurative language; metaphor; song; social criticism.